Pengaruh dari Service Quality, Fun, Memorable Tourist Experience terhadap Hedonic Well-Being - Hielvita Ludiya Ludiya; Nova Eviana (LPPM and Travel Operation Department Universitas Asa Indonesia, 2022)
In modern society, people increasingly participate in vacations and hope to enhance their well-being through tourism experiences. How well-being changes over the course of a vacation. Well-being is operationalized as one of them is hedonic well-being. Service quality is a main aspect when assessing the quality of services, this related with customer expectations on service provider. Memorable tourism experience as an experience which involves memories that tourists acquire after personally experiencing meaningful activities and events. Memorable tourist experience can influences their well-being as hedonic well-being of tourist. Fun refers to the value dimensions, signiﬁes a dimension of enjoyment and happiness during the consumption process derived from an experience is suggested as a positive factor behind hedonic well-being. This is issue important because various kinds of life pressures and goals, so people want to reduce stress and find personal well-being. A longitudinal study need for better research results related this study, measure of fun need capture of multi dimensional. This research aims to analyze “The Effect of Service Quality, Fun and Memorable Tourist Experience on Hedonic Well-Being”. Research method using a quantitative approach. Sampling technique using purposive sampling with sample in this research is 164 respondents that are local tourist on various museums in coverage area of several Old Town tourist attractions. The technique of data analysis is using SmartPLS 3.0. The result of this research shows that service quality, fun and memorable tourist experience have positive and significant effect on hedonic well-being. Discussion of the study findings and implications for academics and practitioners conclude the paper.